Specialization in Economic (Commercial) Judiciary as a Response to Business Needs - Bartosz RYMKIEWICZ (Communications of International Proceedings, 2021)
Economic activity is the basis of every economy; therefore, it is extremely important that the state guarantees its possibility of quick and efficient settlement of disputes. The effectiveness of judicial resolution of economic (commercial) disputes concerns both the quality and professionalism of judges, as well as the speed of dispute resolution. The protracted length of the proceedings constitutes an obstacle to access to justice, which entails additional costs for the parties and has a negative macroeconomic impact on the proper functioning of the internal market. A solution that could significantly accelerate the recognition of commercial cases could be the introduction of specialized commercial courts within the state judicial system. A specialized commercial judiciary can bring you many benefits. The aim of the article is an attempt to define the features that should be characterized by a specialized commercial court, so that it meets the justified needs of business activity as much as possible. For this purpose, a proposal for a specialized model of economic judiciary was developed. The judicial systems of selected European countries were also analysed in order to identify common features with the presented model. The article uses research methods such as content analysis, legal analysis and comparative analysis.
Keywords: Specialized commercial judiciary; economic activity and the judicial system; settlement of commercial cases